Early Exposure to High-Sucrose Diet Leads to Deteriorated Ovarian Health - de Melo, Giuliane Barros; Soares, Jéssica Furtado; Costa, Thamyres Cristhina Lima; Benevides, Renata Ohana Alves; Vale, Caroline Castro; Paes, Antonio Marcus de Andrade; Gaspar, Renato Simões (Frontiers in Endocrinology, 2021)
Background: The metabolic syndrome (MetS) is correlated with disorders of the reproductive system, such as the polycystic ovary syndrome (PCOS). While consumption of a diet rich in carbohydrates is linked to the development of MetS, it is still unclear if this diet leads to ovarian dysfunction and PCOS. Objectives: We investigated the influence of a high-sucrose diet (HSD) on the ovarian milieu of Wistar rats and studied the correlation between high consumption of sugary drink and the prevalence of PCOS in women. Methods: Wistar rats were given standard laboratory diet (CTR, 10% sucrose, n = 8) or HSD (HSD, 25% sucrose, n = 8) from postnatal day 21 to 120. The animals were evaluated weekly to calculate food intake, feed efficiency and weight gain. Both onset of puberty and estrous cycle were monitored. Metabolic serum biochemistry, organ morphometry and ovarian histology were performed upon euthanasia. In parallel, fixed-effects multiple linear regression analysis was carried out using data from Brazilian states (459 state-year observations) to test the correlation between the consumption of sugar-sweetened beverages and the prevalence of PCOS. Results: HSD animals were not obese, but showed increased adipose tissue accumulation, hyperglycaemia and insulin resistance when compared to CTR. Interestingly HSD rats also entered puberty earlier than CTR. Moreover, ovaries from HSD animals had an increased number of atretic antral follicles and cystic follicles, which were correlated with hypertrophy of periovarian adipocytes. Finally, there was a positive correlation between the intake of sugary drinks and prevalence of PCOS in women of reproductive age. Conclusions: HSD ingestion leads to ovarian dysfunction in rats and could be correlated with PCOS in women, suggesting these alterations could lead to public health issues. Therefore, we reinforce the deleterious impact of HSD to the ovarian system and suggest that the reduction of added sugars intake could be beneficial to ovarian health.